2002
DOI: 10.3168/jds.s0022-0302(02)74160-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Timed Artificial Insemination (TAI) Protocols for Management of First Insemination Postpartum

Abstract: Two estrus-synchronization programs were compared and factors influencing their success over a year were evaluated. All cows received a setup injection of PGF2alpha at 39 +/- 3 d postpartum. Fourteen days later they received GnRH, followed in 7 d by a second injection of PGF2alpha. Cows (n = 523) assigned to treatment 1 (modified targeted breeding) were inseminated based on visual signs of estrus at 24, 48, or 72 h after the second PGF2alpha injection. Any cow not observed in estrus was inseminated at 72 h. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
12
2
3
Order By: Relevance
“…This illustrates that an increase in temperature, relative humidity, sunshine radiation and THI, could lead to lengthen DP and ICP by several days (Table 4). Similar findings were reported by Du Bois and Williams (1980), Weller and Folman (1990), Ray et al (1992), Bouraoui et al (2002), Jordan et al (2002), Mishra and Joshi (2009) and Gaafar et al (2011). Thus, calving schedules could be adjusted to minimize the adverse effect of heat stress.…”
Section: Effect Of Climatic Variables On Dry Period and Inter Calvingsupporting
confidence: 89%
“…This illustrates that an increase in temperature, relative humidity, sunshine radiation and THI, could lead to lengthen DP and ICP by several days (Table 4). Similar findings were reported by Du Bois and Williams (1980), Weller and Folman (1990), Ray et al (1992), Bouraoui et al (2002), Jordan et al (2002), Mishra and Joshi (2009) and Gaafar et al (2011). Thus, calving schedules could be adjusted to minimize the adverse effect of heat stress.…”
Section: Effect Of Climatic Variables On Dry Period and Inter Calvingsupporting
confidence: 89%
“…These results were higher than those of some studies (37 and 39%) that use PGF 2α treatment and visual detection of estrus (14,19). Conception rate for dairy heifers receving Al at standing estrus was reported to be 47% (7) and 74% (24).…”
Section: Discussioncontrasting
confidence: 60%
“…Conception rate in this study was higher than most of the TAI protocols in dairy heifers and comparable to breeding after detection of estrus. The fact that application of AI in nulliparous heifers, early in relation to ovulation results in high proportion rate (53.8-58%) of female calves in previous (23, 27) and present study, even though a previous study suggested to be expected less female gender ratio, approximately of 45.8 % (14). In agremeent to this result, increasing the interval from TAI to ovulation in lactating cows has been reported to increase female ratio (24).…”
Section: Discussioncontrasting
confidence: 56%
“…Although the present study had a power of 70% (α = 0.05, β = 30%), the probability of a type II error must be considered, as the likelihood of detecting treatment effects may be limited by the number of cows enrolled in the study. In a study utilizing modified targeted breeding (PGF 2α 14 d before GnRH, followed 7 d later by PGF 2α , detection of estrus and AI, with cows not observed in estrus receiving timed AI at 72 h), Jordan et al (2002) suggested that fertility was reduced in cattle not observed in estrus and receiving timed AI (without administration of GnRH) 72 h after PGF 2α .…”
mentioning
confidence: 99%